Your health today choices in a changing society - Teague, Michael L. 1946-; Mackenzie, Sara L. C.; Rosenthal, David M. (New York, NY McGraw Hill, 2009)
Your mind and body; Your lifestyle and health; Your health at risk; Your relationships and sexuality; Protecting your health; Challenges to your health.
Includes bibliographical references (pages R1-R15) and index.
Keywords: Health education; Health promotion; Y học; Giáo dục sức khỏe